Concept of integrated analysis of financial health of global corporations - Čavlin Miroslav; Jovanović Zoran; Đurović Milan (Ekonomija: teorija i praksa, 2025)
This research focuses on the financial health analysis of multinational corporations within the complexity of the global business environment. An integrated analytical model was developed, encompassing six evaluation dimensions: competitive positioning, benchmarking, variance analysis, time dynamics, structural efficiency, and causal interdependencies among indicators. The methodological framework included qualitative and quantitative analyses of consolidated financial statements, comparative analyses, and trend evaluation. The results demonstrated that traditional unidimensional approaches do not provide sufficiently reliable insight into the true financial condition of multinational corporations, whereas the integrated model allows for a deeper understanding of the interconnected financial and operational indicators. The scientific contribution of this work lies in the theoretical advancement of financial analysis through a systems-based approach, while the practical value is reflected in the improvement of managerial decision-making processes, risk management, and capital allocation in global corporations.